2005
DOI: 10.1158/0008-5472.can-04-3664
|View full text |Cite|
|
Sign up to set email alerts
|

Telomerase-Dependent Virotherapy Overcomes Resistance of Hepatocellular Carcinomas against Chemotherapy and Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand by Elimination of Mcl-1

Abstract: Hepatocellular carcinomas (HCC) are drug-resistant tumors that frequently possess high telomerase activity. It was therefore the aim of our study to investigate the potential of telomerase-dependent virotherapy in multimodal treatment of HCC. In contrast to normal liver, HCC xenografts showed high telomerase activity, resulting in tumor-restricted expression of E1A by a telomerase-dependent replicating adenovirus (hTERT-Ad). Neither tumor necrosis factor-related apoptosisinducing ligand (TRAIL) or chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…Evidence for a differential role of Bak versus Bax in cell death regulation also comes from analyses on BH3-only proteins or bacterial toxins (Cartron et al, 2003b;Gillissen et al, 2003Gillissen et al, , 2007Lindenboim et al, 2005;Pardo et al, 2006). Interestingly, recent studies have shown involvement of Mcl-1, an endogenous Bak inhibitor, in the regulation of TRAIL-induced apoptosis (Henson et al, 2003;Taniai et al, 2004;Wirth et al, 2005;Han et al, 2006;Meng et al, 2007). Similar data are available for Bcl-x L , the second major endogenous inhibitor of Bak .…”
Section: Discussionmentioning
confidence: 88%
“…Evidence for a differential role of Bak versus Bax in cell death regulation also comes from analyses on BH3-only proteins or bacterial toxins (Cartron et al, 2003b;Gillissen et al, 2003Gillissen et al, , 2007Lindenboim et al, 2005;Pardo et al, 2006). Interestingly, recent studies have shown involvement of Mcl-1, an endogenous Bak inhibitor, in the regulation of TRAIL-induced apoptosis (Henson et al, 2003;Taniai et al, 2004;Wirth et al, 2005;Han et al, 2006;Meng et al, 2007). Similar data are available for Bcl-x L , the second major endogenous inhibitor of Bak .…”
Section: Discussionmentioning
confidence: 88%
“…In zebrafish embryos, knockdown of zMcl1a and zMcl-1b substantially increased apoptosis triggered by ectopic expression of the Apo2L/TRAIL homolog zDL1b. Previous work suggests that in human hepatocellular carcinoma-derived cells, 32 human cholangiocarcinoma cells, 31 and NIH3T3 mouse fibroblasts, 30 Mcl-1 is a critical modulator of sensitivity to apoptosis signaling by Apo2L/TRAIL. Hence, endogenous Mcl-1 may be particularly important among prosurvival Bcl-2 family members in controlling apoptosis induction by stimuli that engage both the extrinsic and intrinsic apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Thus, Mcl-1 may be a key modulator of DLinduced apoptosis in cells that require engagement of both the extrinsic and intrinsic pathways for commitment to apoptosis. Furthermore, these results indicate that endogenous zMcl-1a and zMcl-1b play an important role in curtailing apoptosis induction through the cell-intrinsic pathway in early zebrafish embryos.…”
Section: Apo2l/trailmentioning
confidence: 99%
“…19,20 Recently, it has been reported that the E1A protein of human Adenovirus type 5 is capable of downregulating protein levels of Mcl-1 21 followed by induction of apoptosis. Additionally, we showed that this decrease can be therapeutically exploited by combined virochemotherapy, 22 indicating that virus-induced Mcl-1 degradation is a promising tool to support conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 91%